Effect of the Type and Number of Adverse Childhood Experiences and the Timing of Adverse Experiences on Clinical Outcomes in Individuals with Bipolar Disorder - Young-Min Park (Brain Sciences, 2020)
: Studies have reported an association between adverse childhood experiences (ACEs) and the clinical outcomes of bipolar disorder (BD). However, these studies have several limitations; therefore, we aimed to clarify the effect of the type and number of ACEs and the timing of adverse experiences on clinical outcomes in patients with BD. We analyzed the data of patients with BD (N = 2675) obtained from the National Institute of Mental Health: Bipolar Disorder Genetic Association Information Network, Translational Genomic Institute-I, and Translational Genomic Institute-II. All patients had been diagnosed using the Diagnostic Interview for Genetic Studies. ACEs were evaluated using the Childhood Life Events Scale (CLES). We analyzed the relationship between childhood trauma and clinical outcome in patients with and without exposure to ACEs. We found that ACEs had a robust negative effect on clinical outcomes, including earlier age at onset, presence of psychotic episodes, suicide attempts, mixed symptoms or episodes, substance misuse comorbidity, and worse life functioning. Specifically, the number of ACEs had the most significant effect on clinical outcomes; however, specific ACEs, such as physical abuse, had a considerable influence. Moreover, post-childhood adverse experiences had a weaker effect on clinical outcomes than ACEs did. There was an association of ACEs with negative clinical outcomes in patients with BD. This indicates the importance of basic and clinical research on ACEs in patients with BD.